THE ROLE OF PARENTS AND NEIGHBORHOODS IN PREVENTING UNDER-5 NUTRITION DISPARITIES IN VILLAGES & CITIES - Nurulnisa Ayu Alfani; Rita Ariesta; Nurlela Nika Sari (Consilium Sanitatis: Journal of Health Science and Policy, 2024)
Objective: Malnutrition in children under five is one of the main health problems in Indonesia, which can have a major effect on child development. This study aims to analyze the role of parents and the environment in the prevention and management of nutritional disparities among children under five in rural and urban areas. Methods: This study used a quantitative design with a cross-sectional approach and involved 380 parent respondents. The dependent variable in this study is the nutritional status of toddlers measured using the indicator of body weight based on body length (BB/PB), while the independent variables include mother's education, father's education, mother's occupation, father's occupation, family income, access to nutrition information, government nutrition programs, and region of residence. Results: The results showed that 12.1% of toddlers had underweight, 85.3% had normal nutritional status, and 2.6% were overweight. Based on Chi-Square analysis, it was found that father's education, father's occupation, family income, and region of residence had a significant association with under-five nutritional status (p<0.05), while mother's education, mother's occupation, access to nutrition information, and government nutrition programs did not show a significant association. Conclusion: This study suggests the importance of increasing the role of fathers and access to nutrition information in rural areas, as well as the need to increase parental awareness of the importance of good nutrition for the growth and development of toddlers. Government programs related to nutrition are expected to be more evenly distributed throughout Indonesia, especially in rural areas.